Swords and shields: the war between Candidatus Liberibacter asiaticus and citrus - Yanan Hu; Nannan Lu; Kaiqiang Bao; Shuting Liu; Ruimin Li; Ruimin Li; Ruimin Li; Guiyan Huang; Guiyan Huang; Guiyan Huang (Frontiers in Plant Science)
Citrus Huanglongbing (HLB) represents a significant threat to the citrus industry, mainly caused by the phloem-limited bacterium Candidatus Liberibacter asiaticus (CLas). In this review, we summarize recent advances in understanding the relationship between citrus and CLas, particularly examining the functions of Sec-dependent effectors (SDEs) and non-classically secreted proteins (ncSPs) in virulence, as well as their targeted interactions with citrus. We further investigate the impact of SDEs on various physiological processes, including systemic acquired resistance (SAR), reactive oxygen species (ROS) accumulation, vesicle trafficking, callose deposition, cell death, autophagy, chlorosis and flowering. Additionally, we focus on the functional research on specific disease-resistant genes in citrus and the molecular mechanisms underlying disease resistance. Finally, we discuss the existing gaps and unresolved questions regarding citrus-CLas interactions, proposing potential solutions to facilitate the development of HLB-resistant citrus varieties.